2020
DOI: 10.1039/d0nr03771k
|View full text |Cite
|
Sign up to set email alerts
|

A thieno-isoindigo derivative-based conjugated polymer nanoparticle for photothermal therapy in the NIR-II bio-window

Abstract: Photothermal therapy (PTT), a powerful tool for non-invasive cancer treatment, has been recognized as an alternative strategy for cancer therapy in clinic, and it is promoted by optical absorbing agents...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 48 publications
0
28
0
Order By: Relevance
“…In particular, PTAs with NIR‐II (1000–1700 nm) absorbing ability are aroused immense attention due to their minimized photo‐toxicity to healthy tissue and deeper tissue penetration comparing to NIR‐I (700–1000 nm) absorbing PTAs. So far, few numbers of NIR‐II absorbing PTAs based on inorganic materials, [5–16] conjugated polymer NPs [17–26] and supramolecular radicals [27, 28] have been developed, however, these PTAs still suffer from the long‐term safety concern and low reproducibility. Small organic NIR‐II absorbing PTAs are proposed to be the most promising PTAs due to their better biocompatibility and higher biodegradability comparing to inorganic and conjugated polymer PTAs.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, PTAs with NIR‐II (1000–1700 nm) absorbing ability are aroused immense attention due to their minimized photo‐toxicity to healthy tissue and deeper tissue penetration comparing to NIR‐I (700–1000 nm) absorbing PTAs. So far, few numbers of NIR‐II absorbing PTAs based on inorganic materials, [5–16] conjugated polymer NPs [17–26] and supramolecular radicals [27, 28] have been developed, however, these PTAs still suffer from the long‐term safety concern and low reproducibility. Small organic NIR‐II absorbing PTAs are proposed to be the most promising PTAs due to their better biocompatibility and higher biodegradability comparing to inorganic and conjugated polymer PTAs.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, PTAs with NIR‐II (1000–1700 nm) absorbing ability are aroused immense attention due to their minimized photo‐toxicity to healthy tissue and deeper tissue penetration comparing to NIR‐I (700–1000 nm) absorbing PTAs. So far, few numbers of NIR‐II absorbing PTAs based on inorganic materials, [5–16] conjugated polymer NPs [17–26] and supramolecular radicals [27, 28] have been developed, however, these PTAs still suffer from the long‐term safety concern and low reproducibility. Small organic NIR‐II absorbing PTAs are proposed to be the most promising PTAs due to their better biocompatibility and higher biodegradability comparing to inorganic and conjugated polymer PTAs.…”
Section: Introductionmentioning
confidence: 99%
“…Under irradiation at 1064 nm, the SPN exhibited admirable PTT effect with excellent targeting ability for tumor both in vitro and in vivo. [211] In another research, Yang and co-workers reported P169 with thieno-M5 as the acceptor unit. [212] The corresponding SPN exhibited strong absorbance in the NIR-II window with a superior photothermal conversion efficiency of 66.4% under 1064 nm irradiation, thereby leading to efficient PTT performance to cancer cell in vivo.…”
Section: Phototherapymentioning
confidence: 98%
“…[38] Liu and co-workers synthesized P168 based on thieno-M5 (Figure 16). [211] The polymer possessed low optical bandgap with absorption extended to 1100 nm in the NIR-II window ascribing to the intramolecular charge transfer. Then, the surface-functionalized SPN based on P168 was prepared.…”
Section: Phototherapymentioning
confidence: 99%